Prophage (phi 80) induction in Escherichia coli K-12 by specific deoxyoligonucleotides. - Irbe, R M (1981)
A cell preparation that is permeable to proteins and oligonucleotides yet produces infectious phage particles after induction treatments was obtained by plasmolysis of Escherichia coli cells lysogenic for phi 80. When the permeabilized cells were exposed to specific oligo(deoxynucleotides), prophage (phi 80) was induced during further incubation. Of the dinucleotides tested, only d(A-G), d(G-G), and d(I-G) induced prophage. The essential base sequence of the deoxydinucleotides for the induction was determined to be deoxy(purine-G). Among oligo(deoxynucleotides) with unique base composition examined, only oligo(deoxyguanylates) exhibited the inducing activity. Although this specific oligo(deoxynucleotide)-triggered induction occurred in recB- cells, the induction was not detected in recA- cells or in the cells lysogenic for induction-negative phi 80(ind-). Possible biological significance of the oligo(deoxynucleotide)-triggered prophage induction is discussed.